Meat quality of Maremmana young bulls (Acta Scientiarum. Animal Sciences, 2019)
Maremmana is a local Italian breed reared in southern Tuscany and northern Latium. Twenty-two young bulls were reared in pasture system with concentrate supply (PSCS), whereas 20 young bulls were reared in feedlot intensive system (IS) in order test differences between meat typologies. The bulls were slaughtered at 18 months old. The performances at slaughtering were similar between finishing systems. IS bull meat has shown higher cooking loss than PSCS bull meat (p < 0.001), higher moisture content (p < 0.01), and fat (p < 0.001), and lower crude protein (p < 0.001). The SFA, MUFA and PUFA percentage were similar between meat typologies; whereas if considered in mg per 100 gr of muscle MUFA and SFA content was higher in PSCS meat (p < 0.05). Among the Healthy Indices, C18:2/C18:3 was higher in IS System (14.08 vs. 9.77; p < 0.001); the results of the PCA (Principal Component Analysis) of fatty acids composition showed that PSCS meat was characterized by MUFA and SFA, while IS meat was identified by C18:2/C18:3, and Ï‰6/ Ï‰3.